From strain theory to the capacity to aspire: A contribution to the cultural political economy of development. Issue 3 (27th May 2021) - MacNeill, Timothy; O'Connor, Christopher; Frederick, Tyler; James-Charles, Esther
ABSTRACT: The idea of the capacity to aspire (CtA) has recently been used in attempts to incorporate cultural and psychological factors into political and economic theories of community development. When integrated with capabilities and capital assets approaches, CtA can be used to explain psychological and cultural development traps, but may be incomplete in its formulation. Through a theoretical discussion and a case study in a post disaster situation, we show that the integration of strain theory can make CtA more meaningful, nuanced, and powerful in its framing of community development processes. We suggest that this integrated theory offers a more thorough understanding of the cultural political economy of development, and a richer trajectory for future research and practice than does CtA theory alone.